Serial magnetic resonance imaging and single‐photon emission computed tomography findings in a patient with heat stroke. Issue 5 (23rd February 2015) - Nakano, Yumiko; Manabe, Yasuhiro; Hattori, Mizuho; Takahashi, Yoshiaki; Narai, Hisashi; Omori, Nobuhiko; Takeyama, Takahisa; Abe, Koji
Abstract We report on serial changes in magnetic resonance imaging and single‐photon emission computed tomography in a patient with heat stroke. A 66‐year‐old man was admitted for unconsciousness with hyperthermia. He presented with dysarthria and truncal ataxia. Axial diffusion‐weighted imaging showed marked hyperintensity in the vermis and cerebellar hemisphere with a decrease of the apparent diffusion coefficient. Follow‐up magnetic resonance imaging at 165 days after onset showed slowly progressing cerebellar atrophy. Follow‐up single‐photon emission computed tomography at 8 months after onset showed progressing hypoperfusion in the diffuse cerebellar cortex. He became alert, but dysarthria and truncal ataxia persisted. These findings show that cytotoxic edema leads to delayed irreversible neuronal damage in the cerebellum. Our patient demonstrated that heat stroke causes irreversible neuronal damage, especially in the cerebellum.